PENGARUH PENDAPATAN, KESESUAIAN HARGA KEBUTUHAN POKOK, KEBIASAAN BERBELANJA DAN KESADARAN KESEHATAN TERHADAP POLA KONSUMSI - Rahmi, Dina Maulida; Fadjar , Nurman Setiawan (Journal of Development Economic and Social Studies, 2022)
The Covid-19 pandemic has changed how people consume goods and services. In Malang city the outbreak has made numerous changes in supply, demand, and people’s purchasing power, which eventually modify the citizens’ consumption pattern. The objective of this research is to identify the effects of income, price of basic needs, shopping habit, and health awareness on the consumption pattern of Malang people during the Covid-19 pandemic. The data of this quantitative research was harvested from questionnaires distributed to 100 samples. Here the non-parametric statistical analysis, i.e. Spearman’s rank correlation test, was used the relationship between independent and dependent variables. This study finds that all independent variables have positive and significant effects on consumption pattern. Based on the magnitude of relationship between variables, income very strongly influences consumption pattern, while price of basic needs, utilitarian shopping habit, and health awareness strongly affect the consumption pattern, and hedonic shopping habit weakly influences the consumption pattern. The implications of this research are the occurrence of income increase and well-planned purchases according to priority scales. Higher income and better expenditure planning can make people readier to face future economic shock.